THE TRADITION OF MONDAY AND THURSDAY FASTING AT PERAK PRENGGAN MOSQUE, KOTAGEDE: A LIVING HADITH STUDY - Fauzi, Irfan; Saputri, Anggi Setiyani; Supriyanto, Supriyanto (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2022)
Monday and Thursday fasting is the ritual worship encouraged by the Prophet Muhammad Saw. because this fasting is sunnah. So anyone who does it can get the spiritual reward. Something unique has been found in a region, to be exact around the Perak Mosque in the village of Prenggan, Kotagede. Generally, this sunah fasting was done individually as a personal charity, but the society of Prenggan do it together. Finally to deepen society’s understanding about it, the writer researches further with the approach of phenomenon and the case study that become the analysis knife to help understand the social symptoms, the cause, and the purpose of Monday and Thursday fasting culture is still preserved until now. Using descriptive-qualitative methods in living hadith study frames, this research shows that these phenomenons appear from prior experiences that see from the past to be connected through interaction among the community. Then the phenomenon evolved and sustained as an comprehension of society’s intersubjectivity that are connected to each other.Keyword: Monday and Thursday Fasting, Social Phenomenon, Living Hadith.AbstrakPuasa Senin Kamis merupakan ritual ibadah yang dianjurkan oleh Nabi Muhammad Saw. Karena puasa ini bersifat sunnah, maka siapapun yang mengerjakannya akan mendapatkan pahala. Hal unik ditemukan di suatu daerah, tepatnya sekitar Masjid Perak di dusun Prenggan, Kotagede. Lazimnya puasa sunah ini dilakukan secara individual sebagai amal pribadi. Akan tetapi, masyarakat Prenggan melakukan puasa tersebut secara kolektif (bersama-sama). Akhirnya demi mendalami pemahaman masyarakat, penulis meneliti lebih lanjut dengan pendekatan fenomenologi dan studi kasus yang menjadi pisau analisis untuk membantu memahami gejala sosial, sebab, dan tujuan tradisi puasa Senin Kamis masih dilestarikan hingga saat ini. Menggunakan metode kualitatif-deskriptif dalam bingkai studi living hadis, penelitian ini menunjukkan bahwa fenomena ini muncul dengan didasari pengalaman-pengalaman sebelumnya yang melihat dari masa lalu dan dihubungkan melalui proses interaksi sesama masyarakat. Kemudian fenomena tersebut berkembang dan hidup lestari sebagai pemahaman intersubjektivitas masyarakat yang saling terhubung satu sama lain.Kata Kunci: Puasa Senin Kamis, Fenomena Sosial, Living Hadis.